Modeling and numerical analysis for mechanical characterization of soft tissue mechanism applying inverse finite element technique - Mulk, Md.; Islam, Kazi Nusrat; Biswas, Md. Haider Ali (Frontiers in Applied Mathematics and Statistics, 2023)
Tissue mimicking materials (e.g. polyvinyl alcohol cryogel (PVA-C)) are extensively used in clinical applications such as tissue repair, tissue engineering etc. Various mechanical testing techniques have been used to assess the biomechanical compatibility of tissue-mimicking materials. This paper presents the development of inverse finite element (FE) techniques that are solved using numerical optimization to characterize the mechanical properties of PVA-C specimens. Here, a numerical analysis where the displacement influence factor was employed in conjunction with a linear elastic model of finite thickness. In the analysis, the effects of Poisson’s ratio, specimen aspect ratio and relative indentation depth were investigated, and a novel mathematical term was introduced to Sneddon’s equation. In addition, a robust optimization algorithm was developed in MATLAB which utilized FE modelling for parameter estimation before it was rigorously validated.